Out-of-pocket expenses and healthcare service utilisation among maintenance haemodialysis patients: A study at a tertiary care hospital in Udupi, Karnataka - Anandhu K. Ramesan; Brayal D’Souza; Varalakshmi Chandra Sekaran (Journal of Education and Health Promotion, 2024)
Background: Financial burdens faced by patients in India suffering from chronic kidney disease (CKD) are linked to healthcare access and inadequate insurance coverage. This study analyses out-of-pocket expenses and explores their healthcare utilisation patterns. Materials and Method: This time-bound hospital-based cross-sectional study was conducted in a tertiary care hospital in Udupi district, Karnataka, among patients who have undergone haemodialysis (HD) treatment for at least a year. Following ethics approval and CTRI registration, informed consent was obtained from all the patients prior to data collection. Result: The study involved 109 HD patients. The direct medical and non-medical costs incurred by HD patients were Rs 9,400 (IQR = 13,700) and Rs 3,200 (IQR = 2,000), respectively. The monthly health-related OOPE was Rs 16672.0 (IQR = 14,630.0). Overall, 103 (94.5%) individuals had been hospitalised since they began HD, and 50.5% of patients were hospitalised within the past year. On linear regression analysis, it was observed that the joint monthly income (β 0.134, 95% CI 0.007 - 0.182, P value = 0.048), number of dialyses per week (β 1.14, 95% CI 7541.5 - 16551.07, P value < 0.001), and social security (β −1.02, 95% CI −13463.0 - 7982.56, P value < 0.001) exhibited significant correlations and served as predictors for household out-of-pocket expenditure (HROOPE) experienced by the patients. Conclusion: The study concludes that people receiving HD incur a considerable financial cost. Additionally, the CKD population uses healthcare services at a notable rate, including frequent hospital stays, visits to outpatient departments (OPDs), and emergency treatment, underscoring the pressing need for an increase in insurance coverage.